Zirconium in the Nuclear Industry: Thirteenth International Symposium 2002
DOI: 10.1520/stp11415s
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Zirconium Alloy Chemical Composition on Microstructure Formation and Irradiation Induced Growth

Abstract: The studies of the dislocation structure, phase, and microchemical compositions of alloy Zr-1Nb-1.2Sn-0.35Fe (E635) and its modifications containing Fe from 0.15 to 0.65% were carried out before and after research reactor irradiation at ∼350°C to maximal fluence of ∼1027 m-2 (E > 0.1 MeV) and at ∼60°C. The size and concentration of the <a>-type loops depend on the alloy composition and fluence and saturate even at low doses (<1 dpa). The evolution of the <c>-component … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
32
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 12 publications
6
32
0
Order By: Relevance
“…These samples had been irradiated to a fluence of between 8.7 and 14.7 x 10 25 n m -2 for E > 1MeV. Using a conversion of 6.0 x 10 24 n m -2 dpa -1 [23], these damage levels correspond to between 14.5 and 24.5 dpa. [26].…”
Section: Experimental Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These samples had been irradiated to a fluence of between 8.7 and 14.7 x 10 25 n m -2 for E > 1MeV. Using a conversion of 6.0 x 10 24 n m -2 dpa -1 [23], these damage levels correspond to between 14.5 and 24.5 dpa. [26].…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In Zr-Sn, Zr-Nb and Zr-Sn-Nb alloys the addition of more Fe led to a decrease in growth strain [22]. Shishov et al also showed data from the BOR-60 test reactor, which indicated that increased Fe leads to a lower IIG strain in variants of the E635 Nb containing alloy [23].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the authors observed no β-Nb phases within α-Zr when the alloy Nb content is 0.29 wt.% and did observe β-Nb when the Nb content was 0.49 wt.%. This leads to the conclusion that Nb TSS in α-Zr is in the range 0.29-0.49 wt.% at temperatures below the Zr-Nb monotectoid temperature (<600 °C), a value much greater than that suggested by Canay et al Figure 1 Ternary Zr-Nb-Fe diagram generated from data after [3,[20][21][22][23][24][25][26][27]29,[41][42][43][44]46,[62][63][64]. All compositions are given in at.%.…”
Section: Nb Terminal Solid Solubility In α-Zrmentioning
confidence: 99%
“…This designation of β-Nb should be distinguished from the β-Nb that exists after heattreatments below the Zr-Nb monotectoid. The Fe content in β-Nb below the Zr-Nb monotectoid is reported in commercial alloys but only convincingly in phases that were ZrNbFe ternary phases prior to irradiation that had undergone irradiation-induced Fe depletion resulting in a composition such as Zr42Nb50Fe8, at.% [27]. Again, the description of the phase as β-Nb is somewhat ambiguous given that β-Nb has a Nb composition ~85%-90% according to the binary Zr-Nb phase diagram [28].…”
Section: The β-Nb Phase and "Where The Iron Goes"mentioning
confidence: 99%
“…The uniform corrosion is enhanced while the nodular corrosion resistance of neutron irradiated Zr-2 is improved due to the neutron irradiation [22]. Considering the mechanical effects, the zirconium alloys exhibit irradiation hardening [23,24], irradiation growth [2, 25,26], and reduction of plastic anisotropy [27,28].…”
Section: Neutron Irradiation Effectsmentioning
confidence: 99%